PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI THE PREMIER BASKO HOTEL PADANG - nopi acel nopi acel (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
The purpose of this study was to determine the effect of work discipline on employee performance at The Premier Basko Hotel Padang. This type of reseativerch is quantitatitive descriptive with causal assumptions. The sample uses saturated sample technique with 51 people using a questionnaire with a Likert scale. The results showed: (1) Work Disclipine for the very bad category(39,2%), (2) Employee performance in the low category (3,92%), (3) Simple linear regression test value obtained F 461,001 with the value 0.000 signifiance <0.05, so work discipline can be said to be significant, With R Square value of 0,88. This means that employee perfomance is influenced by work discipline as much as 8,8% and 91,2% is influenced by other factors. Then obtained regression coefficient value of 1.568 significance 0.000 < 0.05. This means that each addition of 1 unit of work discipline will add 1,568 employee perfomance.